Detecção e análise filogenética do Chikungunya virus e de Orthoflavivirus durante a vigilância de arbovírus no Brasil - Joilson Xavier dos Santos Junior (2023)
The scenario of co-circulation of different arbovirus species, that have already caused extensive outbreaks in Brazil, has imposed constant challenges to the public health system related to the precise identification and control of the spread of epidemic viruses. Given this context, in order to analyze the genetic diversity and phylogenetic relationships of the Chikungunya virus (CHIKV) this work used the nanopore sequencing technology to generate a total of 454 CHIKV genomes from clinical samples collected in 13 Brazilian states between 2021 and 2022. The phylogenetic analyzes revealed the reintroduction of the East-Central-South-African lineage (ECSA) of CHIKV in the state of Rio Grande do Norte, highlighting its dispersion from the Northeast to the Midwest, and suggesting the Midwest as a source of dissemination of CHIKV to Paraguay. The CHIKV genomic data allowed the reconstruction of the updated evolutionary history of the ECSA lineage in Brazil and revealed that the Northeast region continues to act as the main source of CHIKV dispersion in Brazil, fueling a frequent network of viral exchange between the Northeast and Southeast regions. This work also describes the emergence of two subclates of the ECSA lineage, clade I, more diverse, covers samples from 14 Brazilian states, while clade II is concentrated in the Northeast region in 2022. The comparative analysis revealed the presence of single nucleotide variants among the sequences of both clades, including mutations E1-T98A and E2-V264A, previously associated with increased adaptation of CHIKV to Aedes spp. mosquitoes. In addition, this work also describes the results of the development of a protocol that integrates RT-PCR and nanopore sequencing for the multiplex detection of CHIKV and several viruses belonging to the genus Orthoflavivirus, enabling the accurate identification of different viral lineages in a single reaction. Validation of the protocol with clinical samples positive for DENV-1, DENV-2, CHIKV, YFV and ZIKV resulted in the correct identification of viral lineages in 83% of the samples tested.